A smart device application for the automated determination of E. coli colonies on agar plates. Issue 8 (August 2017) - Austerjost, Jonas; Marquard, Daniel; Raddatz, Lukas; Geier, Dominik; Becker, Thomas; Scheper, Thomas; Lindner, Patrick; Beutel, Sascha
Abstract : The manual counting of colonies on agar plates to estimate the number of viable organisms (so‐called colony‐forming units–CFUs) in a defined sample is a commonly used method in microbiological laboratories. The automation of this arduous and time‐consuming process through benchtop devices with integrated image processing capability addresses the need for faster and higher sample throughput and more accuracy. While benchtop colony counter solutions are often bulky and expensive, we investigated a cost‐effective way to automate the colony counting process with smart devices using their inbuilt camera features and a server‐based image processing algorithm. The performance of the developed solution is compared to a commercially available smartphone colony counter app and the manual counts of two scientists trained in biological experiments. The comparisons show a high accuracy of the presented system and demonstrate the potential of smart devices to displace well‐established laboratory equipment.